PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN DENGAN MENGGUNAKAN KARTU HURUF PADA PEMBELAJARAN BAHASA INDONESIA - F34209443, Rosliniarti; ., Aunurrahman; ., Ngatiyo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The problem with this research is how to increase the capability of reading the beginning by using Card Letter in teaching Indonesian language in 1st grade of 31 State Elementary School, south east of Pontianak. Based on earlier observation the students capability of reading averagely is only found 42%. Subject on this research is Researcher herself/himself as a teacher that teaching reading the beginning of Indonesian Language and 1st grade students of 31st State Elementary School, south east of Pontianak with the total number of students are 20, consist of 11 boys and 9 girls. Researcher helped by colleague as collaborator. Method that use in this research is Descriptive Action and Research in Class (PTK). By following the procedure such as; Planning, Implementation, observation/evaluation and reflection. Technique of collecting/gathering the data is by observing, using data collection tools which is pages of observation against student and teacher (IPKG). Result/Data then analyzed with average percentage capability technique. This research and action in class done in two cycles. Positive results happen in the second cycles of the research. Either increasing the capability of reading the beginning of students or increasing the capability of teacher in implementation of how to teach reading the beginning by using the card letter. Average capability of reading the beginning of students before doing research was 42%, in first cycle increase into 69% and second cycle reach 90%. There for by using card letter is success in increasing capability in reading the beginning of students just like what we expected to be. (like what we hope for) Abstrak:Masalah dalam penelitian ini adalah bagaimana meningkatkan kemampuan membaca permulaan dengan menggunakan kartu huruf pada pembelajaran bahasa Indonesia kelas I sekolah dasar Negeri 31 Pontianak Tenggara. Berdasarkan Observasi awal diidentifikasi rata-rata kemampuan membaca permulaan siswa hanya sekitar 42%.Subjek dalam penelitian ini adalah peneliti sendiri sebagai guru yang mengajar membaca permulaan pada pembelajaran bahasa Indonesia dan siswa kelas I sekolah dasar Negeri 31 Pontianak Tenggara yang berjumlah 20 orang terdiri dari 11 orang laki-laki dan 9 orang perempuan. Peneliti dibantu oleh teman sejawat sebagai kolaborator.Metode yang digunakan pada penelitian ini adalah metode deskriptif dengan bentuk penelitian tindakan kelas (PTK). Dengan mengikuti prosedur yaitu perencanaan, pelaksanaan, observasi/evaluasi dan refleksi. Tekhnik pengumpulan data adalah dengan cara observasi dengan alat pengumpulan data berupa lembar observasi terhadap siswa dan terhadap guru (IPKG). Data dianalisis dengan tekhnik persentase rata-rata kemampuan.Penelitian tindakan kelas ini dilakukan dua siklus . Pada siklus yang kedua barulah penelitian ini dianggap berhasil, baik dari peningkatan kemampuan membaca permulaan siswa maupun peningkatan kemampuan guru dalam menerapkan pembelajaran membaca permulaan dengan menggunakan kartu huruf.Kemampuan rata-rata membaca permulaan siswa pada saat sebelum dilakukan penelitian adalah 42%, pada siklus I meningkat menjadi 69% dan pada siklus II mencapai 90 %. Dengan demikian penggunaan kartu huruf berhasil meningkatkan kemampuan membaca permulaan siswa seperti yang peneliti harapkan. Kata Kunci : Membaca permulaan, kartu huruf